2022
DOI: 10.51878/healthy.v1i3.1461
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Jumlah Leukosit Pada Penderita Demam Tifoid

Abstract: Typhoid fever is caused by infection with the bacterium Salmonella typhi which attacks the digestive tract. Clinical symptoms of typhoid fever are characterized by complaints of fever that occur in the afternoon or evening, with a slow and gradual increase in temperature or commonly called step ladder fever. The diagnosis of typhoid fever is in the form of clinical symptoms, physical examination and laboratory examination. One of the laboratory tests by counting the number of leukocytes. The purpose of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Salmonella terjadi penetrasi ke lapisan mukosa usus, lalu S.typhi akan difagositosis oleh sel fagosit dan ia akan bertahan dalam sel fagosit yang bisa melindunginya untuk melakukan penyebaran ke tubuh dan terlindungi dari antibodi serta agen antimicrobial sehingga tidak ada respon tubuh untuk menaikkan jumlah leukositnya [7]. Konsumsi gizi yang seimbang juga berpengaruh pada proses pembentukan sel leukosit [13].…”
Section: Karakteristik Klinis Pasienunclassified
“…Salmonella terjadi penetrasi ke lapisan mukosa usus, lalu S.typhi akan difagositosis oleh sel fagosit dan ia akan bertahan dalam sel fagosit yang bisa melindunginya untuk melakukan penyebaran ke tubuh dan terlindungi dari antibodi serta agen antimicrobial sehingga tidak ada respon tubuh untuk menaikkan jumlah leukositnya [7]. Konsumsi gizi yang seimbang juga berpengaruh pada proses pembentukan sel leukosit [13].…”
Section: Karakteristik Klinis Pasienunclassified
“…If it is concluded that the patient with typhoid fever with positive results, the number of neutrophils is lower than the number of lymphocytes, and the NLR value is higher. This condition predicts a critical phase of plasma leakage [17]. This study aims to find out the results of the Neutrophil-Lymphocyte Ratio with various expressions of the results of the Immunoglobulin G / Immunoglobulin M Test in typhoid fever sufferers at Haji General Hospital Surabaya.…”
Section: Introductionmentioning
confidence: 99%